Analysis of shortcomings in the strategy and practice of water supply to the population, based on the war experience - Yu. F. Rudenko; N. B. Kasteltseva; A. V. Klisko; T. R. Garanenko (Мінеральні ресурси України)
The problems associated with the quantitative, qualitative, environmental, economic and other aspects of water resources, in particular the quality of drinking water, are of paramount importance today. The amount of water used is many times greater than other extractive resources. Water is the most important substance on our planet, primarily because it is necessary to sustain life. Providing the population with a sufficient amount of good quality drinking water is a strategic task for the national government. Drinking water used for centralised water supply to the population is drawn from surface water sources and groundwater aquifers. Historically, surface water has been preferred as the main source of water supply. The Dnipro River and its numerous tributaries are the main source of water supply for 75% of the Ukrainian population. However, due to significant technogenic pressures on the water quality in the Dnipro River and its catchment area the surface water is characterised as polluted and highly polluted in terms of chemical and bacterial contamination. In order to improve the quality component of the domestic drinking water supply to the population and industrial enterprises (mainly food production), particular attention should be paid to the increased use of groundwater. The experience gained during the war suggests the need to establish a local water supply system based on pumping stations (i.e., buvettes) with reserve water sources and means of delivering water to the consumption network. The article analyses the existing shortcomings and problems in the organisation of domestic drinking water supply in Ukraine and outlines some steps to improve the situation.